2016
DOI: 10.1186/s12955-016-0538-z
|View full text |Cite
|
Sign up to set email alerts
|

The burden of disease in patients eligible for mentalization-based treatment (MBT): quality of life and costs

Abstract: BackgroundMentalization-Based Treatment (MBT) is a promising, though expensive treatment for severely ill patients with Borderline Personality Disorder (BPD). A high burden of disease in terms of quality of life (QoL) and life years lost can be a reason to prioritize mental health interventions, and specifically for BPD patients. Moreover, when the societal costs of the illness are high, spending resources on high treatment costs would be more easily legitimized. Therefore, the purpose of this study was to cal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
20
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 13 publications
(23 citation statements)
references
References 54 publications
2
20
1
Order By: Relevance
“…Although the numerical results varied, the negative results for MBT-DH in the cost-utility outcome and the favourable results in the cost-effectiveness outcome remained stable under the alternative scenarios and in sensitivity analyses. The finding that MBT-DH was slightly superior to S-TAU in terms of cost-effectiveness with remissions as the outcome may seem out of line with the clinical results of the comparison between MBT-DH and S-TAU by Laurenssen et al (2018). In that study, both MBT-DH and S-TAU showed significant improvements on all outcome measures at 18-month follow-up, but MBT-DH was not superior to S-TAU.…”
Section: Discussionmentioning
confidence: 68%
See 4 more Smart Citations
“…Although the numerical results varied, the negative results for MBT-DH in the cost-utility outcome and the favourable results in the cost-effectiveness outcome remained stable under the alternative scenarios and in sensitivity analyses. The finding that MBT-DH was slightly superior to S-TAU in terms of cost-effectiveness with remissions as the outcome may seem out of line with the clinical results of the comparison between MBT-DH and S-TAU by Laurenssen et al (2018). In that study, both MBT-DH and S-TAU showed significant improvements on all outcome measures at 18-month follow-up, but MBT-DH was not superior to S-TAU.…”
Section: Discussionmentioning
confidence: 68%
“…In that study, both MBT-DH and S-TAU showed significant improvements on all outcome measures at 18-month follow-up, but MBT-DH was not superior to S-TAU. The difference between the present cost-effectiveness study and the effectiveness study of Laurenssen et al (2018) is that in the present study effects are measured over a 36-month follow-up, while Laurenssen et al reported on only the first 18 months of follow-up. A number of studies have found that MBT can be more effective after a long period than a short period of follow-up (see, e.g., Bateman & Fonagy, 1999, 2001, 2008, 2009Smits et al, 2019).…”
Section: Discussionmentioning
confidence: 69%
See 3 more Smart Citations